Respuestas

  • Usuario de Brainly
2013-02-12T19:53:53+01:00

ResolVeMos:

a) (x+28) +15 = 2*(x+15)

  x+ 43 = 2x +30

  x-2x = 30 -43

   -x = -13

      x = 13

b) (2x+1) = 8 -(3x+3)

      2x+1 = 8-3x -3

     2x +1 = -3x +5

       2x +3x = 5 -1

        5x = 4

        x = (4/5)

c)   2*(x-7) = 6*(x+1)

       2x -14 = 6x +6

       2x -6x = 6 +14

        -4x = 20

     x = -20/4

      x = -5

d) 2*(x-5) = 5*(x-4)

     2x -10 = 5x -20

      2x -5x = -20 +10

       -3x = -10

         x = 10/3

e)   6*(x-4) = 3*(x-3)

      6x -24 = 3x -9

      6x -3x = -9 +24

        3x = 15

           x  = 15/3

             x = 5

f)   3*(x-3) -4*(x-5) = 6

       3x -9 -4x +20 = 6

         -x +11 =  6

          -x = 6-11

            -x = -5

             x = 5

g) 6*(x-3) +5*(x+4) = 15

      6x -18 +5x +20 = 15

        11x +2 = 15

                 11x = 15-2

                    11x = 13

                        x = 13/11

 SaLuDos :)'